Pedagogical Shift Through Computational Thinking: Reflections of Pre-Service Indonesian Language Teachers - Imam Safi'i; Lili Wahdini (Jurnal Pendidikan Edutama, 2026)
Computational Thinking (CT) is one of the approaches in learning that can be used to train students in solving complex problems into simpler ones so that they can be solved more effectively. Research on the effectiveness of CT in learning has been widely conducted, but reflective research that explores the experiences of prospective language teachers has not been widely found. This study aims to reveal the reflections of prospective Indonesian language teachers when implementing the Computational Thinking (CT) approach in the learning process. This study uses a qualitative approach with a reflective-narrative study design. The data sources in this study are 19 prospective language teachers who are currently participating in education and training organized by a private university in Indonesia. Based on thematic analysis of the results of participant reflections, four main themes were found, namely (1) interesting experiences in implementing CT, (2) challenges and failures faced, (3) changes in mindset and learning strategies, and (4) improving the quality of learning. The results of the study show that although the implementation of CT presents cognitive challenges, the use of CT is able to form systematic mindsets, encourage self-evaluation, and improve the quality of learning design and implementation. This study recommends strengthening practice-based and reflection-based CT training in prospective teacher education.